ANALISIS ANGKA KUMAN PADA TANGAN PEDAGANG LOTEK DI JALAN RAYA ANDALAS KOTA PADANG TAHUN 2020 - sari, mila (Jurnal Ayurveda Medistra, 2020)
Abstract :One potential source of food contamination is from the hands of the handlers. Based on observations made on lotek traders on Jalan Andalas, food handlers' behavior does not pay attention to hygiene when processing lotek, especially on hand hygiene, traders do not wash their hands with running water before processing food, the behavior of traders who directly touch food ingredients without intermediaries (gloves) but directly by hand, and also food consumed in a raw state. This can allow the contamination of germs on the hands of the lotek processed by a handler and can be at risk of disease for consumers. The purpose of this study was to know the number of germs on the hands of lotek traders on Jalan Raya Andalas, Padang City in 2020. This type of research is descriptive. The sample in this study was lotek traders who were on Jalan Raya Andalas, Padang City, amounting to 5 people. The time of the study was January - April 2020. Data collection was obtained from germ sampling at the hands of traders then brought to the laboratory for incubation for 2x24 hours and counted the number of germ colonies, the examination was carried out at the Environmental Health Laboratory of the Health Ministry of Health, Padang. The results of the study after examination of the hands of lotek traders, there are 4 traders who meet the requirements for the number of bacteria on the hands is 89 CFU, 76 CFU, 63 CFU, 93 CFU and 1 trader who does not meet the requirements for the number of bacteria on the hands is 303 CFU.It is expected that traders should always pay attention to hand hygiene such as always washing hands with soap in contact with food, using tools to take food ingredients, no open wounds and not wearing jewelry (rings) Keywords: Food snacks; Germ Number